1983
DOI: 10.1126/science.219.4585.740
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Proteins

Abstract: Both photosynthetic and nonphotosynthetic microorganisms, grown on various carbon and energy sources, are used in fermentation processes for the production of single-cell proteins. Commercial-scale production has been limited to two algal processes, one bacterial process, and several yeast and fungal processes. High capital and operating costs and the need for extensive nutritional and toxicological assessments have limited the development and commercialization of new processes. Any increase in commercial-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 25 publications
1
27
0
3
Order By: Relevance
“…1). Biosurfactant activity was recognized by the occurrence of halo zones surrounding the colonies on YM medium after cultivation at [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] C, slightly at 40 C, but was absent at 45 C. In some reports, thermophilic yeasts are defined as yeasts with a minimal temperature for growth of 20 C but with no maximal temperature limit. By this definition, we concluded that the yeast PY1 strain that grows well at 20 C, and that up to high temperatures, such as 37 C, it is thermotolerant.…”
Section: Growth and Biosurfactant Activity At Various Temperatures Inmentioning
confidence: 99%
“…1). Biosurfactant activity was recognized by the occurrence of halo zones surrounding the colonies on YM medium after cultivation at [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] C, slightly at 40 C, but was absent at 45 C. In some reports, thermophilic yeasts are defined as yeasts with a minimal temperature for growth of 20 C but with no maximal temperature limit. By this definition, we concluded that the yeast PY1 strain that grows well at 20 C, and that up to high temperatures, such as 37 C, it is thermotolerant.…”
Section: Growth and Biosurfactant Activity At Various Temperatures Inmentioning
confidence: 99%
“…This activity represents a promising application of biotechnology, which is even more successful when associated to the utilization of sewage or industrial wastes as substrate (Litchfield, 1983). Anoxygenic phototrophic bacteria, especially Purple NonSulfur Bacteria (PNBS) are widely distributed in nature (soil, water and wastes) and have special importance because of their potential role in the degradation of industrial pollutants (Sasikala et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The cell dry weight was determined asprevious work [14], [15]. Aliquot of the culture media was centrifuged at 5000 rpm for 15 min, after washing the biomass with Ringer serum; it was precipitated for a second time before measuring dry weight, followed by drying of the cells at 105±1º C for 2-3h.…”
Section: E Analyticalmentioning
confidence: 99%